PENGARUH MARKETING SYARIAH DAN RELIGIUSITAS TERHADAP KEPUTUSAN MENABUNG DI USPPS AUSATH BLOKAGUNG TEGALSARI BANYUWANGI - Nurul Inayah; Siti Syarifatul Latifah (Jurnal Ekonomi Syariah Darussalam, 2024)
The purpose of this study is to analyze the influence of: 1) the Sharia Marketing variable (X1) on the Savings Decision variable (Y), 2) the Religious variable (X2) on the Savings Decision variable (Y), 3) the Sharia Marketing variable (X1) and the Religious variable (X2) on the Savings Decision variable (Y). The results of multiple linear regression analysis show that: 1) the Sharia Marketing variable (X1) has a significant effect on the Savings Decision variable (Y), 2) the Religious variable (X2) does not have a significant effect on the Savings Decision variable (Y), 3) from the results of simultaneous testing on the 2 independent variables (X1 and X2) on the dependent variable (Y) has a significant effect. The conclusion is: 1) the variable of Sharia Marketing at USPPS AUSATH Blokagung can increase the decision to save, because there is an indication that customers and employees are equally concerned in paying attention and looking for alternatives to improve the quality of their savings, 2) Employees cannot prioritize religiosity as a whole because they only work, 3) Simultaneously, customers are related and influence each other, so that they can increase the decision to save.